Evolution and sustainability of the olive production systems - Fernandez Escobar R.; de la Rosa R.; Leon L.; Gomez J.A.; Testi F.; Orgaz M.; Gil-Ribes J.A.; Quesada-Moraga E.; Trapero A. (Present and future of the Mediterranean olive sector, 2013)
The olive tree counts among the most important oil-producing crops throughout the Mediterranean region. The century-long presence of olive trees in most producing countries can lead to misunderstanding as to the sustainability, hardiness, longevity and plasticity of their cultivation. At present, olive trees are planted in all regions of the globe between 30 and 45° latitude in the two hemispheres. Olive culture is a complex agrosystem with variability in production systems, cultivation techniques and genetic resources. The evolution of the olive growing sector over time revealed that until the 1950s, the olive culture expanded slowly. After that, traditional planting system have been transformed into more intensive groves. Since the 1990s the trend has been to reconvert traditional orchards into more intensive systems. In the new cultivated areas and in the new producers’ countries, intensive and high density groves are proliferating with the objective of reducing both unproductive periods and costs. In many instances, these changes in the growing systems have been accompanied by irrational exploitation of natural resources and the introduction of new varieties. This report is a review of the different olive growing systems and the evolution from traditional to more intensive production systems.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)